The Influence Of The UTAUT Model,Service Quality, Information Quality, And System Quality To Intention To Adopt And Intention To Use Mobile JKN With Moderation Of Patient Health Value - Lestariningsih, Nuri; Kusuma Dewi, Citra (International Journal of Science, Technology & Management, 2025)
Digitalization of health services offers convenience for users, but not all new technological innovations can be easily accepted by the community. This study aims to assess how the influence of performance expectancy, effort expectancy,social influence,facilitating conditions, service quality, information quality, system quality, patient health value, on intention to adopt and intention to use BPJS Healthparticipants to use the National Health Insurance (JKN)Mobile application. The sampling technique used in the study was purposive sampling, with the population being users of the National Health Insurance (JKN)Mobile application in Indonesia. The data analysis technique used is Structural Equation Modeling Partial Least Square (SEM-PLS),then the research instrument used refers to the UTAUTmodel and the Updated Delone and McLean IS Success Model (modified) used in Alnaser dkk., (2024) study.